The Impact of Green Human Resource Management on Organizational Environmental Performance: The Mediating Role of Employee Pro-Environmental Behavior - Dedi Joko Hermawan; Hidayatul Hikmah (HARAMAIN: Jurnal Manajemen Bisnis, 2026)
This study examines the impact of Green Human Resource Management (GHRM) on organizational environmental performance, with employee pro-environmental behavior as a mediating variable, in the context of PT Surabaya Industrial Estate Rungkut (SIER). A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with a sample of 80 employees. Data were collected through structured questionnaires and analyzed to assess both direct and indirect relationships among variables. The results indicate that GHRM has a positive and significant effect on organizational environmental performance and significantly influences employee pro-environmental behavior. Furthermore, employee pro-environmental behavior is found to have a positive effect on environmental performance and partially mediates the relationship between GHRM and organizational outcomes. This study contributes theoretically by integrating organizational practices and individual behavioral mechanisms into a comprehensive model of environmental performance, particularly within an industrial context in a developing country. Practically, the findings suggest that organizations should enhance sustainability outcomes by strengthening GHRM practices and fostering employee engagement in pro-environmental activities. The study is limited by its sample size and single organizational focus; therefore, future research is recommended to include broader contexts and additional variables. Overall, this research highlights the importance of aligning human resource strategies with environmental objectives to achieve sustainable organizational performance.